Conservation Easements as a Forest Management Strategy - Meadows, C.; Mansius, Donald (Maine Policy Review, 1994)
Conservation easements have become an increasingly popular way of protecting private lands that have public value. Maine, like other northeastern states, has a particular interest in conservation strategies given among other things, its natural resource-dependent economy. C. Edwin Meadows, Commissioner of the Maine Department of Conservation (MDOC), and Donald J. Mansius, the Northern Forest Lands Coordinator for MDOC, address the forest management aspects of conservation easements and provide examples of easement land where forest management is permitted. An accompanying sidebar by Chris Spruce describes a conservation easement that has existed for more than a down years along the Penobscot River in northernMaine.